JURGEN HABERMAS DAN HERMENEUTIKA KRITIS (SEBUAH GERAKAN EVOLUSI SOSIAL) - Ulumuddin, Ulumuddin (Institut Agama Islam Negeri (IAIN) Palu, 2006)
Jurgen Habermas was born in Germany on June 18, 1929. He is a very influential philosopher in contemporary era. He constructed his philosophical thoughts after he had involved inÂ Frankfurt School of Philosophy. Since 1960âs his thoughts on philosophy and social sciences had became more and more influential. He was a type of philosopher who was very critical to Marxism, not only to orthodox-Marxism but also to neo-Marxism.Â He endeavored to adapt Marxâs heritages of thoughts to his time needs. This article will elaborate Habermasâs hermeneutics of critique.Â Kata Kunci: Jurgen Habermas, hermeneutika kritis, filsafat